PENGARUH PENGGUNAAN MEDIA KOMIK TANPA TEKS TERHADAP KETERAMPILAN MENULIS TEKS DIALOG SISWA KELAS IV SD - nur abidah; Widya Karmila sari; Saharullah Saharullah; A.Etika Meidiaty Anugrah (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
This study examines the effect of using comics without text on the writing skills of fourth grade students. The formulation of the problem in this study are: (1) What is the description of the use of comics without text on the skills of writing dialogue texts for fourth grade students of SD Inpres BTN IKIP 1 Kota Makassar?; (2) What is the description of the results of the students' dialogue text writing skills in SD Inpres BTN IKIP 1 Kota Makassar?; (3) What is the effect of using comics without text on the dialogue text writing skills of fourth graders of SD Inpres BTN IKIP I Kota Makassar?. The objectives of this research are; This study aims to determine the description and influence of the use of comics without text on the skills of writing dialogue texts for fourth grade students of SD Inpres BTN IKIP 1 Kota Makassar. This study uses a quantitative research with the type of research is True Experiment with a research design of Pretest-Posttest Control Group Design. The population in this study were all fourth grade students using the simple random sampling method, where grade IV A consisted of 34 students and class IV B consisted of 32 students, so that the total sample was 66 students. Data were collected using a research instrument in the form of a dialogue text writing skill test. Technical analysis of the data used the Independent Sample t-test technique with the help of the IBM SPSS Statistic Version 16 application. The results of the descriptive analysis of the description of dialogue text writing skills showed the writing skills of fourth graders of SD Inpres BTN IKIP I Kota Makassar using comics media without text categorized as high and the learning process runs very effectively. The results and conclusions show that there is an effect of comics without text on students' dialogue text writing skills in the experimental class when compared to the control class that does not use comics without text.